Book tower images : Visualizing Henry van de Velde's Ghent University library tower. - Tentoonstelling. Gent. Vandenhove Centre for architecture and art; Bass-Krueger, Maude, 1985-; Jacobs, Steven, 1967-; Dossche, Charlotte, 1991- (Gent : A&S/Books, 2023)
The Ghent University library with its famous "Book Tower" was designed by Henry van de Velde in the 1930s. It re-opened recently after a long restoration process under the supervision of Robbrecht en Daem architecten. Book Tower Images focuses on the rich artistic imagery of the monument. Over the years, leading artists and photographers such as Frans Masereel, Lucien Hervé, Candida Höfer, and Carl De Keyzer have visualized it abundantly. Jan De Cock, Marie-Jo Lafontaine, Anne Teresa De Keersmaeker and others realized installations or dance performances in the building that were documented with the help of photographs and films. Juxtaposing multiple images of the same building, Book Tower Images deals with various models of architectural representation: from typical modernist architectural photographs by Emile Sergysels from the 1940s to recent explorations by Dirk Braeckman, Geert Goiris, Aglaia Konrad, and Walter Vorjohann among many others. 'Book Tower Images' combines architectural photography with a myriad of other artistic and photographic practices such as documentary photography, street photography, fashion shoots, photojournalism, amateur photography, painting, drawing, video, film et cetera - with, of course, the Book Tower as leitmotiv. Exhibition: Vandenhove - Ghent University, Belgium (20.04. - 17.06.2023).
20.04.2023 - 17.06.2023
boek
Keywords: van de Velde, Henry; Architecture -- 20th century -- Pictorial works; Rijksuniversiteit te Gent. -- Bibliotheek -- Buildings; Library architecture -- Belgium -- Ghent -- Exhibitions; Exhibitions